A polycultural theory of wisdom based on Habermas's worldview. (June 2020) - Li, Kang; Wang, Fengyan; Wang, Zhendong; Shi, Juan; Xiong, Mimi
Building on Habermas's worldview, this paper attempts to construct a theory of wisdom that integrates the advantages of Eastern and Western cultures. To this end, we review previous definitions of wisdom and their problems and analyze the importance of worldview for wisdom. A worldview provided by the German philosopher Jürgen Habermas is eminently persuasive. We argue that Habermas's worldview provides a more suitable basis for a polycultural theory of wisdom. The specific components of the wisdom theory are: (1) a relationalist belief in the universal world; (2) transcendental agency in the subjective world; (3) intersubjective communication orientation in the social world; and (4) integrated principles of certainty and uncertainty in the objective world. Inspired by this theory, people could adopt different principles for their subjective, social, and objective worldviews and coordinate them to deal with the problems of human survival, which would also promote the long-term flourishing of human civilization.